“Preocupación por la imagen corporal y adicción al entrenamiento en fisicoculturistas de la ciudad de Riobamba”. - Armas Silva, Irma Nathaly (2017)
The objective of this current research is to analyze corporal image concern and addictive training in some bodybuilders from Riobamba city. The sample consisted of 28 bodybuilders who were preparing for different fitness events. They were selected under non-experimental, cross-sectional, field research and bibliographic design which conducted to descriptive research. Techniques to collect data were: “Adonis Questionnaire”, which identified levels of corporal image concern in bodybuilders, and the Training Addiction Scale in order to determine addictive training levels in the participants. After the application and tabulation of data, the following results were obtained: 39% accounted for a moderate body image concern. Meanwhile 64% presented a medium level of addiction to training. Consequently, it is concluded that bodybuilding demands constant training since it is a demanding sport. It is clear that the concern for body image has an impact on the addiction to training.